Expert Teams in the Academic Library: Going Beyond Subject Expertise to Create Scaffolded Instruction - Wissinger, Christina L.; Raish, Victoria; Miller, Rebecca K.; Borrelli, Steve (Journal of library administration, 2018)
This article explores the way librarians define, leverage, and amplify expertise in a twenty-first century academic library. An expert team comprised of a nursing librarian, online learning librarian, information-literacy librarian, and assessment librarian sorted the learning outcomes from the Information-Literacy Competency Standards for Nursing created by the Health Sciences Interest Group taskforce of the Association of College and Research Libraries (ACRL) by grade-levels. Results found distinguishing experts within a library supports the customization of scaffolded instruction. Additionally, using expert teams in academic libraries supports the larger mission of universities to integrate libraries into teaching and research.